Evolving Dharma Consciousness of Dharmaputra Yudhishthira within the Mahabharata - Sahgal, Smita (Advances in Social Sciences Research Journal, 2020)
The objective of the paper to comprehend a deep implication of what dharma meant to Yudhishthira through the length of historical events related to war and philosophical questioning on the issue. He had to fight through so much in terms of pitting his intuitive understanding of dharma against a whole gamut of mundane ideas of what dharma stood for. For instance, his struggle with his brothers on the complexity of svadhrama and its rejoinder in form of sukshadharma or knowledge of subtle consciousness. His inner conflict continued and there came a time in the last parva, Svargarohana parva, when he just denounced dharma. It was through these trials and tribulations that Yudhishthira was finally able to evolve his own idea of what real truth, conduct, duty, morality and inner consciousness were about. In other words what was true dharma. Through this paper the author attempts to tease out complexities of the philosophical queries that bothered Yudhishthira and also trace his historical trajectory in the quest. The method of investigation would include historicizing the text. This means locating our source, the Mahabharata, on a time line and within a geographical expanse so that we get an idea when the logic of dharma mutated and in what particular region. The text had an expansive period of formulation right from the 8th Century BCE to 4th Century CE, that is, what we understand as the Gupta period. But the text had many later regional recensions as well. We are primarily looking at the older Sanskrit version of the text as recorded in V.S.Sukthankar edited Critical edition (Bhandarkar Oriental edition, Poona) of the Mahabharata. The exercise also requires reading of the magnum opus, locating the usage of the term in association with Yudhishthira and raising some significant issues. These may include queries such as what is dharma according to the Mahabharata. Is definition fixed or is it dynamic? Do all people speak of it with the same voice? Is the notion of dharma same for Yuthishthira and his Pandava brothers? Does his wife. Draupadi, subscribe to his idea of dharma? If his notion of dharma changes over time, does it have anything to do with changing consciousness of the society or at least some people within the society? Can we get a sense of a subtle move towards a shift from karma yoga to jnana yoga and finally to bhakti yoga? In this changing paradigm where do we locate the dharma philosophy of Dharmaputra Yudhishthira, especially as there comes a time when he himself begins questioning the idea of dharma? In a sense his character brings out the dilemmas arising out of the differences in meanings and approaches of comprehending the complexities associated with the concept of dharma. Another point of our methodology would be to understand the etymology of the term dharma and its location in the ancient language. The Sanskrit root of the word is dhr, 'to support', 'to sustain'. In other words, it means that whereby whatever lives, is sustained, upheld, supported. More often than not, the word dharma in its ancient usage denoted the moral realm in its widest sense, meaning both morality as an ideal— man's eternal quest for the good, the right, the just—as well as the given, actual framework of norms, rules, maxims, principles that guide human action. It was integral to the doctrine of purushartha or that of the four goals of a human being; these being artha (success/material possessions), kama (passion/procreation), dharma (virtue/religious duty), moksha (self-perfection). All the four are intertwined. Throughout the epic we witness the evolution of Yudhishthira’s notion of true dharma. What comes out strongly is his holding fast to the value of nonviolence (anrishṃsya), his identification with the sukshma or subtle nature of dharma, his insistence on constricted use of brute force as a part of Kshatriya dharma, his ultimate benevolence towards his family and people. These were actually revealed to be the cause of his indisputable success in Dharma’s recurrent tests. Somewhere by the end of the epic, Yudhishthira’s error in entering into the game of dice, getting in conflict with his brothers on the issue of his duty and not being able to answer Draupadi’s queries initially appear as stepping stones in self-realization to a deeper understanding of what dharma as duty, conduct, search for truth and morality were all about. The orderly world of dharma, which was so central to his character, was eventually arrived at only through repeated trials and tribulations